(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
On behalf of the Department of Social Sciences of the National Academy of Sciences of the Kyrgyz Republic, I heartily congratulate you on the publication of the collection of materials for the International Congress «Traditional Culture and Art: Problems of Preservation and Development», which is held as part of the World Festival of Traditional Culture and Music «Ruh Sanat»!